Manajemen seni pertunjukan Kraton Yogyakarta sebagai penanggulangan krisis pariwisata budaya - Sutiyono, Sutiyono (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This study was aimed at investigating the management which was used to do the traditional performing art in Yogyakarta palace as a form of overcoming the cultural tourism crisises. The research used qualitative approach. Participant obser- vations, indepth interviews, documentation study were conducted to collect data. The results show that the management which was used to doing the traditional per- forming arts in Yogyakarta palace used management functions, like performance programe (planning), performance actuating, performance organize (organizing), and performance controll (controlling). The management applications could be used by Yogyakarta palace as a form of overcoming the cultural tourism crisises.